2014
DOI: 10.1192/bjp.bp.112.121855
|View full text |Cite
|
Sign up to set email alerts
|

One-day cognitive–behavioural therapy self-confidence workshops for people with depression: randomised controlled trial

Abstract: Self-confidence workshops appear promising in terms of clinical effectiveness, cost-effectiveness and access by difficult-to-engage groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 43 publications
(64 reference statements)
6
60
3
Order By: Relevance
“…The CBT--I workshop evaluated in the current study represents a format that provides effective psychological therapy in the community in a way that is both cost--effective and accessible. Similar evidence has been reported in support of CBT workshops for depression (Horrell et al, 2013), indicating the potentially broad application of psychological therapy in this format. In recent years services have been moving towards greater access to psychological therapy, for example the Increasing Access to Psychological Therapies service (IAPT) which has adopted…”
Section: Clinical Implications and Future Directionssupporting
confidence: 80%
See 1 more Smart Citation
“…The CBT--I workshop evaluated in the current study represents a format that provides effective psychological therapy in the community in a way that is both cost--effective and accessible. Similar evidence has been reported in support of CBT workshops for depression (Horrell et al, 2013), indicating the potentially broad application of psychological therapy in this format. In recent years services have been moving towards greater access to psychological therapy, for example the Increasing Access to Psychological Therapies service (IAPT) which has adopted…”
Section: Clinical Implications and Future Directionssupporting
confidence: 80%
“…Studies have shown that these one--day CBT group workshops have been effective in reducing depression and anxiety (Brown, Cochrane & Hancox, 2000;Brown et al, 2004;Horrell et al, 2013), with improvements being maintained two years later (Brown et al, 2008).…”
Section: Access To Treatment For Insomniamentioning
confidence: 99%
“…Over the last 15 years there has been an increase in research on the effectiveness of cognitivebehavioural interventions aimed at raising levels of self-esteem showing that this form of treatment is of value (Brown et al, 2008;Fennell, 1997Fennell, , 1999Horrell et al, 2014;Pack & Condren, 2014;Waite, McManus, & Shafran, 2012). Whilst self-esteem remained a significant factor in predicting distress, this study also demonstrates the importance of attending to metacognitions about worry and self-critical rumination independent of the level of self-esteem.…”
Section: Potential Role Of Metacognitive Therapy As An Alternative Tomentioning
confidence: 59%
“…Of note is that previous studies found that self-referral and more particularly non-stigmatising self-referral, increased access for ethnic minority communities [39,40] .

“ they never recommended it to us in the first place you know cause they were in one of the practices in included in the programme but they never recommended it to us uh you know so that’s why I thought well I’d go and see if we were eligible to go on it.

…”
Section: Resultsmentioning
confidence: 99%